Stratification features of the Meotian sediments of the Southern Ukraine by ostracodas - Vernyhorova, Yu.V.; Kovalenko, V.A. (Reports of the National Academy of Sciences of Ukraine, 2015)
The generalized species composition data, vertical distribution features, and paleoecological characteristics of the ostracoda complexes in the Meotian regiostage sediments of the Southern Ukraine are presented. The ostracod associations distinguished by the ecological characteristics and the biostratigraphical criteria, which provide dating the sediments, are identified.